An Analysis of Data Acquisition System of Temperature, Oxygen, and Carbon Dioxide in Refrigerator with Arduino Mega 2560 - Suciyati, Sri Wahyu; Hidayatullah, Muhammad Syarif; Pauzi, Gurum Ahmad (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
The influence of storage room conditions can cause the quality of post-harvest fruit to decline, so monitoring is necessary. Monitoring is carried out using a data acquisition system designed to measure the temperature, oxygen, and carbon dioxide in the refrigerator storage room automatically. System design is divided into two stages, namely hardware design and software design. The hardware is composed of a sensor unit, a data processing unit (Arduino Mega 2560), and a display unit. On the other hand, the software uses the Arduino IDE. The test results of temperature (DS18B20), oxygen (Figaro KE-25), and carbon dioxide (MH-Z14a) from the system obtained an accuracy value of 98.29% with an error of 1.71%; 98.57% with an error of 1.43%, and 94.58% with an error of 5.42%. The device can display real-time measurement data output to 20x4 LCD with IIC and save the data on a micro-SD card.